ANALISIS RASIO PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN SEKTOR PROPERTY YANG TERDAFTAR DI BEI 2020-2021 - Aldayanti, Nur; Azis, Muhammad; Dunakhir, Samirah (Jurnal Sains Riset, 2024)
This research aims to analyze Profitability Ratios, company size on financial performance which is measured using the activity ratio of property companies listed on the Indonesia Stock Exchange for the 2020-2021 period. The data collection technique is carried out using the documentation method, namely by looking at the required data, then recording and analyzing the published annual financial reports of property sector companies listed on the Indonesia Stock Exchange for the 2020-2021 period. The data analysis technique is carried out using SPSS application statistical tests such as the Classic Assumption Test and Hypothesis Test. The population of this research is all property sector companies listed on the Indonesian Stock Exchange. Meanwhile, the sample determination in this study used a purposive sampling technique and there were only twenty companies that met the criteria. The results of this research show Y = 10.476 + 0.046X1 + 0.015 X2 + 0.436X3. Based on the results of the research conducted, the results obtained were that Return on Assets (ROA), Return on Equity (ROE) and company size simultaneously had a positive and significant effect on the company value of property sector companies listed on the Indonesia Stock Exchange for the 2020-2021 period with a value of the significance level of 0.003 is smaller than 0.05. So it can be concluded that Return on Assets (ROA), Return on Equity (ROE) and company size simultaneously have a significant effect on company performance. Furthermore, the results of data tests that have been carried out using multiple linear regression analysis show that the regression coefficient value for the variables Return on Assets (ROA), Return on Equity (ROE) and company size is 0.046. Assuming that the variables Return on Assets (ROA), Return on Equity (ROE) and company size are constant. This shows that Return on Assets (ROA), Return on Equity (ROE), company size partially influence company performance.